2023
DOI: 10.3390/ijms24043830
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor Tyrosine Kinase Inhibitor Sensitivity Prediction Model Identifies AXL Dependency in Leukemia

Abstract: Despite incredible progress in cancer treatment, therapy resistance remains the leading limiting factor for long−term survival. During drug treatment, several genes are transcriptionally upregulated to mediate drug tolerance. Using highly variable genes and pharmacogenomic data for acute myeloid leukemia (AML), we developed a drug sensitivity prediction model for the receptor tyrosine kinase inhibitor sorafenib and achieved more than 80% prediction accuracy. Furthermore, by using Shapley additive explanations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Recent research endeavors utilizing disease-centric and drug-specific biological attributes have exhibited notable predictive efficacy. 4 , 5 , 6 , 7 , 8 Nevertheless, these methodological approaches necessitate substantial investment in terms of time and resources and demand a synergetic collaboration between researchers in the fields of biology and data science to ensure the effectiveness and rationality of the strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research endeavors utilizing disease-centric and drug-specific biological attributes have exhibited notable predictive efficacy. 4 , 5 , 6 , 7 , 8 Nevertheless, these methodological approaches necessitate substantial investment in terms of time and resources and demand a synergetic collaboration between researchers in the fields of biology and data science to ensure the effectiveness and rationality of the strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the integration of machine learning (ML) in drug discovery has revolutionized the identification and prediction of kinase inhibitors; including those targeting FLT3. Nasimian et al [18] demonstrated the potential of a machine learning-based model in predicting drug sensitivity, revealing crucial insights into AXL dependency in AML. Janssen et al [19] introduced the Drug Discovery Maps (DDM) model, employing algorithms like t-SNE to visualize and predict interactions across the kinase family, leading to the discovery of potent FLT3 inhibitors.…”
Section: Introductionmentioning
confidence: 99%